PESONA KENANGAN YANG TAK TERLUPAKAN MELALUI PEMASARAN BERBASIS PENGALAMAN ALA AHADIAT HOTEL & BUNGALOW, BANDUNG - Yenli Megawati; Novita Novita (Journal of Business & Applied Management, 2016)
Bandung is a developing city that has a lot of attractions. One of them is the beauty of nature. AhadiatHotel & Bungalows has a different concept to other hotel in Bandung. Located in Sukajadi which isjust 10 kilometers from the center of city, Ahadiat Hotel & Bungalow impressed of its uniquenessbecause it is out of the noise but still accessible to the city. This study investigates whether theexperiential marketing effect on customer loyalty. Respondents in this study were 107 customers whostayed at Ahadiat Hotel & Bungalow, Bandung. The results showed that the experiential marketing ofAhadiat Hotel & Bungalow effect on customer satisfaction. And customer satisfaction affects customerloyalty to stayed at Ahadiat Hotel & Bungalow, Bandung.Keywords: experiential marketing, satisfaction, loyalty